Biochemical Diversity of Chenopodiaceae Species: Insights into Adaptation and Biodiversity - Orujova T. Y.; Gurbanova U. A. (BIO Web of Conferences)
The Chenopodiaceae family exhibits great biochemical diversity, which contributes to the successful adaptation of species to diverse and extreme conditions, such as arid, saline and high-temperature climates. The main mechanisms include the control of C4 photosynthesis, which improves water use efficiency and reduces photosynthesis under external conditions. The biochemical adaptation of Chenopodiaceae species provides insight into their ecological significance and potential use in biotechnology, especially for enhancing crop resilience to climate change. Understanding the biochemical diversity of Chenopadiaceae not only sheds light on their evolutionary success, but also provides strategies to address contemporary challenges in agriculture and conservation.